(untitled) (Confluenţe Bibliologice, 2017)
Popular art deserves to be discovered, collected and kept from generations to generations. The author describes 19 types of wooden spoons made by the popular craftsman Marian Viorel from Fălticeni. These spoons have a millenary signiﬁcance and represent various symbols: The Solar Symbol, The Rooster, The Life’s Circle, The Eagle, The Owl, The Snake, The Symbol of Happiness, etc.